The earliest cotton fibers and Pan-regional contacts in the Near East - Liu, Li; Levin, Maureece J.; Klimscha, Florian; Rosenberg, Danny (Frontiers in Plant Science, 2022)
Fiber technology (cordage and textile) has played a central role in all human societies for thousands of years, and its production, application and exchange have deep roots in prehistory. However, fiber remains have only rarely been observed in prehistoric sites because they tend to decay quickly in normal environmental conditions. To overcome preservation problems of macroscopic remains, we employed microbotanical analysis on soils from anthropogenic sediments in activity areas at Tel Tsaf in the Jordan Valley, Israel (ca. 5,200–4,700 cal BC), and recovered fiber microremains. This includes at least two types of bast fibers and the earliest evidence of cotton in the Near East, some of which were dyed in various colors. Some of these fibers likely represent the remnants of ancient clothing, fabric containers, cordage, or other belongings. The cotton remains, probably derived from wild species originating in South Asia, predate the oldest known cotton domestication in the Indus Valley by about two millennia. Tel Tsaf played a pivotal role in trans-regional trade and exchange networks in the southern Levant, and the presence of cotton at the site points to possible connections with the Indus Valley as early as 7,200 years ago.